Sanghuangporus vitexicola sp. nov. (Hymenochaetales, Basidiomycota) from tropical Taiwan - Wu, Sheng-Hua; Wei, Chia-Ling; Chang, Chiung-Chih (Phytotaxa, 2020)
Sanghuangporus vitexicola (Hymenochaetales) is described as a new species based on collections made from Pingtung County, tropical South Taiwan. All studied basidiocarps grew on living trunks of Vitex negundo. This new species is characterized by having perennial, pileate basidiocarps; pore surface yellowish brown, pores 6–8 per mm; context 0.7–1.5 cm thick; setae ventricose to subulate, dark brown, 17–30 × 5–8 μm; basidiospores broadly ellipsoid, brownish, smooth, 4.2–4.8 × 3.2–3.7 μm, with 0.2–0.5 μm thick walls. Maximum likelihood and Bayesian inference phylogenies inferred from the internal transcribed spacer (ITS) region of rDNA indicated that six strains of Sanghuangporus viexicola formed a monophyletic group which is sister to S. zonatus. An identification key to known species of Sanghuangporus is provided.